Analisis Pengaruh Temperatur Ambient Terhadap Kinerja Cooling Tower Unit 2 Berdasarkan Evaluasi Range dan Approach pada PLTGU PT Mitra Energi Batam - Firman Manahan Panjaitan; Putra, Irwanto Zarma (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Negeri Batam, 2025)
PLTGU PT. Mitra Energi Batam has observed that Cooling Tower Unit 2 tends to produce hot steam in larger quantities compared to Unit 1. The greater production of hot steam in Cooling Tower Unit 2 certainly cannot be separated from the influence of ambient temperature (surrounding air temperature). Where the temperature around the Cooling Tower Unit 2 environment affects the performance of the Cooling Tower. The cooler the environment, the better the cooling tower performance. This research aims to determine the extent of influence of ambient temperature on the performance of Cooling Tower Unit 2 in terms of Range and Approach calculations and to evaluate the difference between